Immunogenicity and Efficacy of TNX-1800, A Live Virus Recombinant Poxvirus Vaccine Candidate, against SARS-CoV-2 Challenge in Nonhuman Primates - Awasthi, Mayanka; Macaluso, Anthony; Myscofski, Dawn; Prigge, Jon; Koide, Fusataka; Noyce, Ryan S.; Fogarty, Siobhan; Stillwell, Helen; Goebel, Scott J.; Daugherty, Bruce; Nasar, Farooq; Bavari, Sina; et al. (Vaccines (Basel), 2023)
TNX-1800 is a synthetically derived live recombinant chimeric horsepox virus (rcHPXV) vaccine candidate expressing Wuhan SARS-CoV-2 spike (S) protein. The primary objective of this study was to evaluate the immunogenicity and efficacy of TNX-1800 in two nonhuman primate species challenged with USA-WA1/2020 SARS-CoV-2. TNX-1800 vaccination was well tolerated with no serious adverse events or significant changes in clinical parameters. A single dose of TNX-1800 generated humoral responses in African Green Monkeys and Cynomolgus Macaques, as measured by the total binding of anti-SARS-CoV-2 S IgG and neutralizing antibody titers against the USA-WA1/2020 strain. In addition, a single dose of TNX-1800 induced an interferon-gamma (IFN-γ)-mediated T-cell response in Cynomolgus Macaques. Following challenge with SARS-CoV-2, African Green and Cynomolgus Macaques exhibited rapid clearance of virus in the upper and lower respiratory tract. Future studies will assess the efficacy of TNX-1800 against newly emerging variants and demonstrate its safety in humans.